Problem of Generating Interest in and Motivation for Physical Training Lessons in High School Students - Щирба, В. А. (Physical Education Theory and Methodology, 2016)
The research objective is to study the factors that effect pupils’ interest in physical education and sports. Research methods: questionnaires and surveys, analysis of literary sources. The experiment took place at boarding school-lyceé No. 23 “Kadetskyi Korpus”. The participants were 100 high school students. Research results. The students’ low motivation for activity is conditioned by certain factors whose effect can vary in proportions depending on the youth’s living conditions, environment, and family upbringing. The analysis of reasons behind the high school students’ dissatisfaction with the forms of physical education allows to determine the incentives that help increase the students’ activity. Their answers reveal the need for physical load, active games, and presence of their favorite types of exercises at the lesson, background music, contests, etc.